Factors influencing temporal changes in chemical composition of biogenic deposits in the middle Tążyna River Valley (Kuyavian Lakeland, central Poland) - Okupny, Daniel; Rzepecki, Seweryn; Borówka, Ryszard Krzysztof; Forysiak, Jacek; Twardy, Juliusz; Fortuniak, Anna; Tomkowiak, Julita (Geologos, 2016)
The present paper discusses the influence of geochemical properties on biogenic deposits in the Wilkostowo mire near Toruń, central Poland. The analysed core has allowed the documentation of environmental changes between the older part of the Atlantic Period and the present day (probably interrupted at the turn of the Meso- and Neoholocene). In order to reconstruct the main stages in the sedimentation of biogenic deposits, we have used stratigraphic variability of selected litho-geochemical elements (organic matter, calcium carbonate, biogenic and terrigenous silica, macro- and micro-elements: Na, K, Mg, Ca, Fe, Mn, Cu, Zn, Pb, Cr and Ni). The main litho-geochemical component is CaCO3; its content ranges from 4.1 per cent to 92 per cent. The variability of CaCO3 content reflects mainly changes in hydrological and geomorphological conditions within the catchment area. The effects of prehistoric anthropogenic activities in the catchment of the River Tążyna, e.g., the use of saline water for economic purposes, are recorded in a change from calcareous gyttja into detritus-calcareous gyttja sedimentation and an increased content of lithophilous elements (Na, K, Mg and Ni) in the sediments. Principal component analysis (PCA) has enabled the distinction the most important factors that affected the chemical composition of sediments at the Wilkostowo site, i.e., mechanical and chemical denudation processes in the catchment, changes in redox conditions, bioaccumulation of selected elements and human activity. Sediments of the Wilkostowo mire are located in the direct vicinity of an archaeological site, where traces of intensive settlement dating back to the Neolithic have been documented. The settlement phase is recorded both in lithology and geochemical properties of biogenic deposits which fill the reservoir formed at the bottom of the Parchania Canal Valley.